Open Science by Design: Realizing a Vision for 21st Century Research - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Openness and sharing of information are fundamental to the progress of science and to the effective functioning of the research enterprise. The advent of scientific journals in the 17th century helped power the Scientific Revolution by allowing researchers to communicate across time and space, using the technologies of that era to generate reliable knowledge more quickly and efficiently. Harnessing today's stunning, ongoing advances in information technologies, the global research enterprise and its stakeholders are moving toward a new open science ecosystem. Open science aims to ensure the free availability and usability of scholarly publications, the data that result from scholarly research, and the methodologies, including code or algorithms, that were used to generate those data. Open Science by Design is aimed at overcoming barriers and moving toward open science as the default approach across the research enterprise. This report explores specific examples of open science and discusses a range of challenges, focusing on stakeholder perspectives. It is meant to provide guidance to the research enterprise and its stakeholders as they build strategies for achieving open science and take the next steps.
Keywords: Policy for Science and Technology

Sexual Harassment of Women: Climate, Culture, and Consequences in Academic Sciences, Engineering, and Medicine - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Over the last few decades, research, activity, and funding has been devoted to improving the recruitment, retention, and advancement of women in the fields of science, engineering, and medicine. In recent years the diversity of those participating in these fields, particularly the participation of women, has improved and there are significantly more women entering careers and studying science, engineering, and medicine than ever before. However, as women increasingly enter these fields they face biases and barriers and it is not surprising that sexual harassment is one of these barriers. Over thirty years the incidence of sexual harassment in different industries has held steady, yet now more women are in the workforce and in academia, and in the fields of science, engineering, and medicine (as students and faculty) and so more women are experiencing sexual harassment as they work and learn. Over the last several years, revelations of the sexual harassment experienced by women in the workplace and in academic settings have raised urgent questions about the specific impact of this discriminatory behavior on women and the extent to which it is limiting their careers. Sexual Harassment of Women explores the influence of sexual harassment in academia on the career advancement of women in the scientific, technical, and medical workforce. This report reviews the research on the extent to which women in the fields of science, engineering, and medicine are victimized by sexual harassment and examines the existing information on the extent to which sexual harassment in academia negatively impacts the recruitment, retention, and advancement of women pursuing scientific, engineering, technical, and medical careers. It also identifies and analyzes the policies, strategies and practices that have been the most successful in preventing and addressing sexual harassment in these settings.
Keywords: Policy for Science and Technology; Behavioral and Social Sciences

Integrating Social and Behavioral Sciences Within the Weather Enterprise - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Our ability to observe and forecast severe weather events has improved markedly over the past few decades. Forecasts of snow and ice storms, hurricanes and storm surge, extreme heat, and other severe weather events are made with greater accuracy, geographic specificity, and lead time to allow people and communities to take appropriate protective measures. Yet hazardous weather continues to cause loss of life and result in other preventable social costs. There is growing recognition that a host of social and behavioral factors affect how we prepare for, observe, predict, respond to, and are impacted by weather hazards. For example, an individual's response to a severe weather event may depend on their understanding of the forecast, prior experience with severe weather, concerns about their other family members or property, their capacity to take the recommended protective actions, and numerous other factors. Indeed, it is these factors that can determine whether or not a potential hazard becomes an actual disaster. Thus, it is essential to bring to bear expertise in the social and behavioral sciences (SBS)—including disciplines such as anthropology, communication, demography, economics, geography, political science, psychology, and sociology—to understand how people's knowledge, experiences, perceptions, and attitudes shape their responses to weather risks and to understand how human cognitive and social dynamics affect the forecast process itself. Integrating Social and Behavioral Sciences Within the Weather Enterprise explores and provides guidance on the challenges of integrating social and behavioral sciences within the weather enterprise. It assesses current SBS activities, describes the potential value of improved integration of SBS and barriers that impede this integration, develops a research agenda, and identifies infrastructural and institutional arrangements for successfully pursuing SBS-weather research and the transfer of relevant findings to operational settings.
Keywords: Earth Sciences; Behavioral and Social Sciences

Understanding the Long-Term Evolution of the Coupled Natural-Human Coastal System: The Future of the U.S. Gulf Coast - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The U.S. Gulf Coast provides a valuable setting to study deeply connected natural and human interactions and feedbacks that have led to a complex, interconnected coastal system. The physical landscape in the region has changed significantly due to broad-scale, long-term processes such as coastal subsidence and river sediment deposition as well as short-term episodic events such as hurricanes. Modifications from human activities, including building levees and canals and constructing buildings and roads, have left their own imprint on the natural landscape. This coupled natural-human coastal system and the individual aspects within it (physical, ecological, and human) are under increased pressure from accelerating environmental stressors such as sea level rise, intensifying hurricanes, and continued population increase with its accompanying coastal development. Promoting the resilience and maintaining the habitability of the Gulf Coast into the future will need improved understanding of the coupled natural-human coastal system, as well as effective sharing of this understanding in support of decision-making and policies. Understanding the Long-term Evolution of the Coupled Natural-Human Coastal System presents a research agenda meant to enable a better understanding of the multiple and interconnected factors that influence long-term processes along the Gulf Coast. This report identifies scientific and technical gaps in understanding the interactions and feedbacks between human and natural processes, defines essential components of a research and development program in response to the identified gaps, and develops priorities for critical areas of research.
Keywords: Earth Sciences; Environment and Environmental Studies

Frontiers in Decadal Climate Variability: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Many factors contribute to variability in Earth's climate on a range of timescales, from seasons to decades. Natural climate variability arises from two different sources: (1) internal variability from interactions among components of the climate system, for example, between the ocean and the atmosphere, and (2) natural external forcings, such as variations in the amount of radiation from the Sun. External forcings on the climate system also arise from some human activities, such as the emission of greenhouse gases (GHGs) and aerosols. The climate that we experience is a combination of all of these factors. Understanding climate variability on the decadal timescale is important to decision-making. Planners and policy makers want information about decadal variability in order to make decisions in a range of sectors, including for infrastructure, water resources, agriculture, and energy. In September 2015, the National Academies of Sciences, Engineering, and Medicine convened a workshop to examine variability in Earth's climate on decadal timescales, defined as 10 to 30 years. During the workshop, ocean and climate scientists reviewed the state of the science of decadal climate variability and its relationship to rates of human-caused global warming, and they explored opportunities for improvement in modeling and observations and assessing knowledge gaps. Frontiers in Decadal Climate Variability summarizes the presentations and discussions from the workshop.
Keywords: Earth Sciences

America's Future in Civil Space: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Since the National Research Council released the report America’s Future in Space: Aligning the Civil Space Program with National Needs in 2009, numerous changes have occurred in the civil space arena. In May 2017, the National Academies of Sciences, Engineering, and Medicine convened a workshop on America’s Future in Civil Space with several objectives, including reviewing the history of U.S. space policy and how it might form a broad policy basis for twenty-first century leadership in space, examining the balance and interfaces between fundamental scientific research in space, human space exploration, robotic exploration, earth observations, and applications of space technology and civil space systems for societal benefits, and discussing the value, purpose, and goals of international cooperation in space. The workshop participants sought to capture what has changed, determine how to harness new opportunities, and decisively inform and encourage bold and timely implementation. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Space and Aeronautics

Future Water Priorities for the Nation: Directions for the U.S. Geological Survey Water Mission Area - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Solving problems related to use of water resources will be of paramount importance in coming decades as increasing pressure from growing populations, climate change, extreme weather, and aging water-related infrastructure threaten water availability and quality. The Water Mission Area (WMA) of the U.S. Geological Survey (USGS) has a long-established reputation for collecting and delivering high-quality, unbiased scientific information related to the nation's water resources. WMA observations help inform decisions ranging from rapid responses during emergencies such as hurricanes, floods, and forest fires, to the long-term management of water resources. Produced at the request of USGS, this report identifies the nation's highest-priority water science and resources challenges over the next 25 years. Future Water Priorities for the Nation summarizes WMA's current water science and research portfolio, and recommends strategic opportunities for WMA to more effectively address the most pressing challenges.
Keywords: Earth Sciences

New Worlds, New Horizons in Astronomy and Astrophysics - National Research Council (The National Academies Press, 2010)
Driven by discoveries, and enabled by leaps in technology and imagination, our understanding of the universe has changed dramatically during the course of the last few decades. The fields of astronomy and astrophysics are making new connections to physics, chemistry, biology, and computer science. Based on a broad and comprehensive survey of scientific opportunities, infrastructure, and organization in a national and international context, New Worlds, New Horizons in Astronomy and Astrophysics outlines a plan for ground- and space- based astronomy and astrophysics for the decade of the 2010's. Realizing these scientific opportunities is contingent upon maintaining and strengthening the foundations of the research enterprise including technological development, theory, computation and data handling, laboratory experiments, and human resources. New Worlds, New Horizons in Astronomy and Astrophysics proposes enhancing innovative but moderate-cost programs in space and on the ground that will enable the community to respond rapidly and flexibly to new scientific discoveries. The book recommends beginning construction on survey telescopes in space and on the ground to investigate the nature of dark energy, as well as the next generation of large ground-based giant optical telescopes and a new class of space-based gravitational observatory to observe the merging of distant black holes and precisely test theories of gravity. New Worlds, New Horizons in Astronomy and Astrophysics recommends a balanced and executable program that will support research surrounding the most profound questions about the cosmos. The discoveries ahead will facilitate the search for habitable planets, shed light on dark energy and dark matter, and aid our understanding of the history of the universe and how the earliest stars and galaxies formed. The book is a useful resource for agencies supporting the field of astronomy and astrophysics, the Congressional committees with jurisdiction over those agencies, the scientific community, and the public.
Keywords: Space and Aeronautics

Environmental Engineering for the 21st Century: Addressing Grand Challenges - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Environmental engineers support the well-being of people and the planet in areas where the two intersect. Over the decades the field has improved countless lives through innovative systems for delivering water, treating waste, and preventing and remediating pollution in air, water, and soil. These achievements are a testament to the multidisciplinary, pragmatic, systems-oriented approach that characterizes environmental engineering. Environmental Engineering for the 21st Century: Addressing Grand Challenges outlines the crucial role for environmental engineers in this period of dramatic growth and change. The report identifies five pressing challenges of the 21st century that environmental engineers are uniquely poised to help advance: sustainably supply food, water, and energy; curb climate change and adapt to its impacts; design a future without pollution and waste; create efficient, healthy, resilient cities; and foster informed decisions and actions.
Keywords: Engineering and Technology; Earth Sciences

Exoplanet Science Strategy - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The past decade has delivered remarkable discoveries in the study of exoplanets. Hand-in-hand with these advances, a theoretical understanding of the myriad of processes that dictate the formation and evolution of planets has matured, spurred on by the avalanche of unexpected discoveries. Appreciation of the factors that make a planet hospitable to life has grown in sophistication, as has understanding of the context for biosignatures, the remotely detectable aspects of a planet's atmosphere or surface that reveal the presence of life. Exoplanet Science Strategy highlights strategic priorities for large, coordinated efforts that will support the scientific goals of the broad exoplanet science community. This report outlines a strategic plan that will answer lingering questions through a combination of large, ambitious community-supported efforts and support for diverse, creative, community-driven investigator research.
Keywords: Space and Aeronautics

Thriving on Our Changing Planet: A Decadal Strategy for Earth Observation from Space - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
We live on a dynamic Earth shaped by both natural processes and the impacts of humans on their environment. It is in our collective interest to observe and understand our planet, and to predict future behavior to the extent possible, in order to effectively manage resources, successfully respond to threats from natural and human-induced environmental change, and capitalize on the opportunities – social, economic, security, and more – that such knowledge can bring. By continuously monitoring and exploring Earth, developing a deep understanding of its evolving behavior, and characterizing the processes that shape and reshape the environment in which we live, we not only advance knowledge and basic discovery about our planet, but we further develop the foundation upon which benefits to society are built. Thriving on Our Changing Planet presents prioritized science, applications, and observations, along with related strategic and programmatic guidance, to support the U.S. civil space Earth observation program over the coming decade.
Keywords: Space and Aeronautics

Strategic Investments in Instrumentation and Facilities for Extraterrestrial Sample Curation and Analysis - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The United States possesses a treasure-trove of extraterrestrial samples that were returned to Earth via space missions over the past four decades. Analyses of these previously returned samples have led to major breakthroughs in the understanding of the age, composition, and origin of the solar system. Having the instrumentation, facilities and qualified personnel to undertake analyses of returned samples, especially from missions that take up to a decade or longer from launch to return, is thus of paramount importance if the National Aeronautics and Space Administration (NASA) is to capitalize fully on the investment made in these missions, and to achieve the full scientific impact afforded by these extraordinary samples. Planetary science may be entering a new golden era of extraterrestrial sample return; now is the time to assess how prepared the scientific community is to take advantage of these opportunities. Strategic Investments in Instrumentation and Facilities for Extraterrestrial Sample Curation and Analysis assesses the current capabilities within the planetary science community for sample return analyses and curation, and what capabilities are currently missing that will be needed for future sample return missions. This report evaluates whether current laboratory support infrastructure and NASA's investment strategy is adequate to meet these analytical challenges and advises how the community can keep abreast of evolving and new techniques in order to stay at the forefront of extraterrestrial sample analysis.
Keywords: Space and Aeronautics

Recapturing a Future for Space Exploration: Life and Physical Sciences Research for a New Era - National Research Council (The National Academies Press, 2011)
More than four decades have passed since a human first set foot on the Moon. Great strides have been made in our understanding of what is required to support an enduring human presence in space, as evidenced by progressively more advanced orbiting human outposts, culminating in the current International Space Station (ISS). However, of the more than 500 humans who have so far ventured into space, most have gone only as far as near-Earth orbit, and none have traveled beyond the orbit of the Moon. Achieving humans' further progress into the solar system had proved far more difficult than imagined in the heady days of the Apollo missions, but the potential rewards remain substantial. During its more than 50-year history, NASA's success in human space exploration has depended on the agency's ability to effectively address a wide range of biomedical, engineering, physical science, and related obstacles—an achievement made possible by NASA's strong and productive commitments to life and physical sciences research for human space exploration, and by its use of human space exploration infrastructures for scientific discovery. The Committee for the Decadal Survey of Biological and Physical Sciences acknowledges the many achievements of NASA, which are all the more remarkable given budgetary challenges and changing directions within the agency. In the past decade, however, a consequence of those challenges has been a life and physical sciences research program that was dramatically reduced in both scale and scope, with the result that the agency is poorly positioned to take full advantage of the scientific opportunities offered by the now fully equipped and staffed ISS laboratory, or to effectively pursue the scientific research needed to support the development of advanced human exploration capabilities. Although its review has left it deeply concerned about the current state of NASA's life and physical sciences research, the Committee for the Decadal Survey on Biological and Physical Sciences in Space is nevertheless convinced that a focused science and engineering program can achieve successes that will bring the space community, the U.S. public, and policymakers to an understanding that we are ready for the next significant phase of human space exploration. The goal of this report is to lay out steps and develop a forward-looking portfolio of research that will provide the basis for recapturing the excitement and value of human spaceflight—thereby enabling the U.S. space program to deliver on new exploration initiatives that serve the nation, excite the public, and place the United States again at the forefront of space exploration for the global good.
Keywords: Space and Aeronautics

Improving Characterization of Anthropogenic Methane Emissions in the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Understanding, quantifying, and tracking atmospheric methane and emissions is essential for addressing concerns and informing decisions that affect the climate, economy, and human health and safety. Atmospheric methane is a potent greenhouse gas (GHG) that contributes to global warming. While carbon dioxide is by far the dominant cause of the rise in global average temperatures, methane also plays a significant role because it absorbs more energy per unit mass than carbon dioxide does, giving it a disproportionately large effect on global radiative forcing. In addition to contributing to climate change, methane also affects human health as a precursor to ozone pollution in the lower atmosphere. Improving Characterization of Anthropogenic Methane Emissions in the United States summarizes the current state of understanding of methane emissions sources and the measurement approaches and evaluates opportunities for methodological and inventory development improvements. This report will inform future research agendas of various U.S. agencies, including NOAA, the EPA, the DOE, NASA, the U.S. Department of Agriculture (USDA), and the National Science Foundation (NSF).
Keywords: Earth Sciences; Environment and Environmental Studies

Sustaining Ocean Observations to Understand Future Changes in Earth's Climate - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The ocean is an integral component of the Earth's climate system. It covers about 70% of the Earth's surface and acts as its primary reservoir of heat and carbon, absorbing over 90% of the surplus heat and about 30% of the carbon dioxide associated with human activities, and receiving close to 100% of fresh water lost from land ice. With the accumulation of greenhouse gases in the atmosphere, notably carbon dioxide from fossil fuel combustion, the Earth's climate is now changing more rapidly than at any time since the advent of human societies. Society will increasingly face complex decisions about how to mitigate the adverse impacts of climate change such as droughts, sea-level rise, ocean acidification, species loss, changes to growing seasons, and stronger and possibly more frequent storms. Observations play a foundational role in documenting the state and variability of components of the climate system and facilitating climate prediction and scenario development. Regular and consistent collection of ocean observations over decades to centuries would monitor the Earth's main reservoirs of heat, carbon dioxide, and water and provides a critical record of long-term change and variability over multiple time scales. Sustained high-quality observations are also needed to test and improve climate models, which provide insights into the future climate system. Sustaining Ocean Observations to Understand Future Changes in Earth's Climate considers processes for identifying priority ocean observations that will improve understanding of the Earth's climate processes, and the challenges associated with sustaining these observations over long timeframes.
Keywords: Earth Sciences

Gaseous Carbon Waste Streams Utilization: Status and Research Needs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In the quest to mitigate the buildup of greenhouse gases in Earth's atmosphere, researchers and policymakers have increasingly turned their attention to techniques for capturing greenhouse gases such as carbon dioxide and methane, either from the locations where they are emitted or directly from the atmosphere. Once captured, these gases can be stored or put to use. While both carbon storage and carbon utilization have costs, utilization offers the opportunity to recover some of the cost and even generate economic value. While current carbon utilization projects operate at a relatively small scale, some estimates suggest the market for waste carbon-derived products could grow to hundreds of billions of dollars within a few decades, utilizing several thousand teragrams of waste carbon gases per year. Gaseous Carbon Waste Streams Utilization: Status and Research Needs assesses research and development needs relevant to understanding and improving the commercial viability of waste carbon utilization technologies and defines a research agenda to address key challenges. The report is intended to help inform decision making surrounding the development and deployment of waste carbon utilization technologies under a variety of circumstances, whether motivated by a goal to improve processes for making carbon-based products, to generate revenue, or to achieve environmental goals.
Keywords: Environment and Environmental Studies

Next Generation Earth System Prediction: Strategies for Subseasonal to Seasonal Forecasts - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
As the nation's economic activities, security concerns, and stewardship of natural resources become increasingly complex and globally interrelated, they become ever more sensitive to adverse impacts from weather, climate, and other natural phenomena. For several decades, forecasts with lead times of a few days for weather and other environmental phenomena have yielded valuable information to improve decision-making across all sectors of society. Developing the capability to forecast environmental conditions and disruptive events several weeks and months in advance could dramatically increase the value and benefit of environmental predictions, saving lives, protecting property, increasing economic vitality, protecting the environment, and informing policy choices. Over the past decade, the ability to forecast weather and climate conditions on subseasonal to seasonal (S2S) timescales, i.e., two to fifty-two weeks in advance, has improved substantially. Although significant progress has been made, much work remains to make S2S predictions skillful enough, as well as optimally tailored and communicated, to enable widespread use. Next Generation Earth System Predictions presents a ten-year U.S. research agenda that increases the nation's S2S research and modeling capability, advances S2S forecasting, and aids in decision making at medium and extended lead times.
Keywords: Earth Sciences

Assessment of the National Science Foundation's 2015 Geospace Portfolio Review - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
At the request of the Advisory Committee for Geosciences of the National Science Foundation (NSF), a review of the Geospace Section of the NSF Division of Atmospheric and Geospace Sciences was undertaken in 2015. The Portfolio Review Committee was charged with reviewing the portfolio of facilities, research programs, and activities funded by Geospace Section and to recommend critical capabilities and the balance of investments needed to enable the science program articulated in the 2013 NRC decadal survey Solar and Space Physics: A Science for a Technological Society. The Portfolio Review Committee's report Investments in Critical Capabilities for Geospace Science 2016 to 2025 (ICCGS) was accepted by the Advisory Committee for Geosciences in April 2016. Assessment of the National Science Foundation's 2015 Geospace Portfolio Review provides an independent assessment of the ICCGS report. This publication assesses how well the ICCGS provides a clear set of findings, conclusions, and recommendations for Geospace Section that align with the science priorities of the NRC decadal survey, and adequately take into account issues such as the current budget outlook and the science needs of the community. Additionally, this study makes recommendations focused on options and considerations for NSF's implementation of the ICCGS recommendations.
Keywords: Space and Aeronautics

Report Series: Committee on Astronomy and Astrophysics: Small Explorer Missions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The 2010 astronomy and astrophysics decadal survey, New Worlds, New Horizons in Astronomy and Astrophysics, laid out an exciting portfolio of recommended activities to guide the agencies’ research programs over the period 2012-2021. The newly constituted Committee on Astronomy and Astrophysics (CAA) is tasked with monitoring the progress of the survey’s recommended priorities. The CAA met in conjunction with Space Science Week 2017 in Washington, D.C., on March 28- 30, 2017. This was the first meeting at which the CAA could produce a report, and in advance of that meeting, the CAA received a question from NASA about an upcoming Small Explorer (SMEX) mission call. This report addresses whether there may or may not be sufficient compelling science motivations for a SMEX-sized mission to justify a SMEX Announcement of Opportunity (AO) in 2018 or 2019 (as is currently planned).
Keywords: Space and Aeronautics

A Decision Framework for Managing the Spirit Lake and Toutle River System at Mount St. Helens - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The 1980 eruption of Mount St. Helens in southwest Washington State radically changed the physical and socio-economic landscapes of the region. The eruption destroyed the summit of the volcano, sending large amounts of debris into the North Fork Toutle River, and blocking the sole means of drainage from Spirit Lake 4 miles north of Mount St. Helens. As a result of the blockage, rising lake levels could cause failure of the debris blockage, putting the downstream population of approximately 50,000 at risk of catastrophic flooding and mud flows. Further, continued transport of sediment to the river from volcanic debris deposits surrounding the mountain reduces the flood carrying capacity of downstream river channels and leaves the population vulnerable to chronic flooding. The legacy of the 1980 eruption and the prospect of future volcanic, seismic, and flood events mean that risk management in the Spirit Lake Toutle River system will be challenging for decades to come. This report offers a decision framework to support the long-term management of risks related to the Spirit Lake and Toutle River system in light of the different regional economic, cultural, and social priorities, and the respective roles of federal, tribal, state, and local authorities, as well as other entities and groups in the region. It also considers the history and adequacy of characterization, monitoring, and management associated with the Spirit Lake debris blockage and outflow tunnel, other efforts to control transport of water and sediment from the 1980 and later eruptions, and suggests additional information needed to support implementation of the recommended decision framework.
Keywords: Environment and Environmental Studies; Earth Sciences